The Effectiveness of Love Languages on Mu’asyarah bil Ma’ruf Behavior in Realizing Marital Harmony among the Millennial Generation: A Maqashid al-Shariah Perspective - Alfa Singgani L.Irade; Gasim Yamani; Sahran Raden (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2026)
This study examines the effectiveness of love languages in shaping Mu’asyarah bil Ma‘ruf behavior to achieve marital harmony among the millennial generation from the perspective of Maqashid al-Shariah theory, with a case study conducted in Wani Satu Village, Tanantovea District. The study aims to analyze the role of love languages and the Maqashid al-Shariah perspective in fostering family harmony among millennial couples in the village. This research employs a qualitative approach. Data were collected through interviews, observations, and documentation. The data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings indicate that the application of love languages in Mu’asyarah bil Ma‘ruf behavior can serve as an effective effort to promote marital harmony among millennial families. The concept of love languages consists of five forms of expression: words of affirmation, quality time, receiving gifts, acts of service, and physical touch. In Islam, the purpose of marriage is to establish a family characterized by sakinah (tranquility), mawaddah (affection), and rahmah (compassion), which can be achieved through good and respectful behavior between spouses.